Knockout of secretin receptor reduces biliary damage and liver fibrosis in Mdr2−/− mice by diminishing senescence of cholangiocytes. (November 2018) - Zhou, Tianhao; Wu, Nan; Meng, Fanyin; Venter, Julie; Giang, Thao; Francis, Heather; Kyritsi, Konstantina; Wu, Chaodong; Franchitto, Antonio; Alvaro, Domenico; Marzioni, Marco; Onori, Paolo; et al.
Abstract Secretin receptor (SR), only expressed by cholangiocytes, plays a key role in the regulation of biliary damage and liver fibrosis. The aim of this study was to determine the effects of genetic depletion of SR in Mdr2−/− mice on intrahepatic biliary mass, liver fibrosis, senescence, and angiogenesis. 12 wk SR−/−, Mdr2−/−, and SR−/− /Mdr2−/− mice with corresponding wild-type mice were used for the in vivo studies. Immunohistochemistry or immunofluorescence was performed in liver sections for (i) biliary expression of SR; (ii) hematoxylin and eosin; (iii) intrahepatic biliary mass by CK-19; (iv) fibrosis by Col1a1 and α-SMA; (v) senescence by SA-β-gal and p16; and (vi) angiogenesis by VEGF-A and CD31. Secretin (Sct) and TGF-β1 levels were measured in serum and cholangiocyte supernatant by ELISA. In total liver, isolated cholangiocytes or HSCs, we evaluated the expression of fibrosis markers (FN-1 and Col1a1); senescence markers (p16 and CCL2); microRNA 125b and angiogenesis markers (VEGF-A, VEGFR-2, CD31, and vWF) by immunoblots and/or qPCR. In vitro, we measured the paracrine effect of cholangiocyte supernatant on the expression of senescent and fibrosis markers in human hepatic stellate cells (HHSteCs). The increased level of ductular reaction, fibrosis, and angiogenesis in Mdr2−/− mice was reduced in SR−/− /Mdr2−/− mice. Enhanced senescence levels in cholangiocytes from Mdr2−/− mice were reversed to normal in SR−/− /Mdr2−/− mice. However, senescence was decreased in HSCs from Mdr2−/− mice but returned to normal values in SR−/− /Mdr2−/− mice. In vitro treatment of HHSteCs with supernatant from cholangiocyte lacking SR (containing lower biliary levels of Sct-dependent TGF-β1) have decreased fibrotic reaction and increased cellular senescence. Sct-induced TGF-β1 secretion was mediated by microRNA 125b. Our data suggest that differential modulation of angiogenesis-dependent senescence of cholangiocytes and HSCs may be important for the treatment of liver fibrosis in cholangiopathies. In this study the authors demonstrate that the secretin/secretin receptor axis plays a regulatory role in biliary proliferation and liver fibrosis through differential changes in the senescence of cholangiocytes and hepatic stellate cells in a mouse model of primary sclerosing cholangitis. Targeting senescent cholangiocytes by modulation of the secretin/secretin receptor axis may provide a key therapeutic approach in the treatment of cholestatic liver diseases.